Current limits of experimental research into habits and future directions. (April 2018) - Watson, P; de Wit, S
Highlights: Insensitivity to devaluation could be due to habits or weak goal-directed control. Limited direct evidence for habits as a function of behavioral repetition in humans. We suggest alternative paradigms to measure cue-driven, value-insensitive behavior. Abstract : The outcome devaluation paradigm allows for the differentiation between goal-directed actions and habits and has been used extensively in both animal and human studies. This has been a fruitful avenue of research with translational human research reporting reduced sensitivity to devaluation in a number of clinical populations using various different paradigms. However, these paradigms do not provide a direct window on the extent to which impaired performance is due to strong habit formation or to weak goal-directed control. We review the indirect nature of the existing evidence from both animal and human studies and suggest avenues for future research including combining behavioral repetition with manipulations to reduce goal-directed control processes as well as alternative paradigms such as the Pavlovian-to-instrumental transfer task.